2008
DOI: 10.2172/1001211
|View full text |Cite
|
Sign up to set email alerts
|

Fuel-Flexible Combustion System for Co-production Plant Applications

Abstract: Future high-efficiency, low-emission generation plants that produce electric power, transportation fuels, and/or chemicals from fossil fuel feed stocks require a new class of fuelflexible combustors. In this program, a validated combustor approach was developed which enables single-digit NO x operation for a future generation plants with low-Btu off gas and allows the flexibility of process-independent backup with natural gas. This combustion technology overcomes the limitations of current syngas gas turbine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…It was developed by the Air Force Research Laboratory and General Electric Aircraft Engines in the U.S. [3,4] , and has been widely studied for aircraft engine applications [5][6][7] , recently also for stationary gas turbine combustor applications as well [8,9] . Detailed experimental tests have demonstrated that trapped vortex combustor has extraordinary performances, such as high combustion efficiency, low NOx emission, reduced lean blow out, increase in altitude re-light, and so on [10] .…”
Section: Introductionmentioning
confidence: 99%
“…It was developed by the Air Force Research Laboratory and General Electric Aircraft Engines in the U.S. [3,4] , and has been widely studied for aircraft engine applications [5][6][7] , recently also for stationary gas turbine combustor applications as well [8,9] . Detailed experimental tests have demonstrated that trapped vortex combustor has extraordinary performances, such as high combustion efficiency, low NOx emission, reduced lean blow out, increase in altitude re-light, and so on [10] .…”
Section: Introductionmentioning
confidence: 99%